Biomarkers of kidney disease - Edelstein, Charles L. (Charles Louis) (Academic Press is an imprint of Elsevier, 2017)
A biomarker is a molecule that is measured as a marker of normal biological processes, disease processes or the response to a diagnostic or therapeutic intervention. Kidney diseases like acute kidney injury, chronic kidney disease, diabetic nephropathy, glomerular disease, renal cancer and preeclampsia still have a high morbidity. Measurement of biomarkers in the blood or urine that detect patients at risk of kidney diseases or that detect kidney diseases in the earliest stage may ultimately result in preventative or earlier or more effective treatments for kidney diseases. Biomar.